Booms and Busts in the UK Housing Market. - Muellbauer, J; Murphy, A (CEPR, 1997)
The often volatile behaviour of UK house prices between 1957 and 1994 is analysed in an annual econometric model. Theory suggests that financial liberalization of mortgage markets in the 1980s should have led to notable shifts in house price behaviour. The evidence supports the predictions of theory, suggesting shifts took place in wealth effects, as in the consumption function, and that real interest rates and income expectations became more important. The presence of transactions costs suggests important non-linearities in house price dynamics. The paper also contains an explicit econometric treatment of expectations, demography, supply spillovers from the rented sector and of composition biases in the official house price index.